2005
DOI: 10.1159/000084649
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitric Oxide and Oxidative Stress in the Regulation of Blood Pressure and Renal Function in Prehypertensive Ren-2 Transgenic Rats

Abstract: Aims: The present study was performed to evaluate the role of nitric oxide (NO) and its interaction with superoxide anion (O2) in the regulation of blood pressure (BP) and renal function during the developmental phase of hypertension in Ren-2 transgenic rats (TGR). The first aim was to compare BP and renal functional responses to acute NO synthase (NOS) inhibition achieved by intravenous (i.v.) infusion of Nω-nitro-L-arginine-methyl ester (L-NAME) in prehypertensive heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…9 In contrast, blockade of NO synthesis decreases T regulatory cells, worsens renal damage and increases blood pressure in rats. [10][11][12] Studies have also demonstrated an important regulatory role for NO in cutaneous functions. Previous studies showed that NO stimulates keratinocyte migration in vitro, 13 while deficiency in iNOS delays cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, blockade of NO synthesis decreases T regulatory cells, worsens renal damage and increases blood pressure in rats. [10][11][12] Studies have also demonstrated an important regulatory role for NO in cutaneous functions. Previous studies showed that NO stimulates keratinocyte migration in vitro, 13 while deficiency in iNOS delays cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…16 Increased production of ROS has been reported in human essential hypertension, as well as in animal models of genetic and acquired hypertension. 13,1721 Increased levels of ROS are caused not only by enhanced oxidant activity, but also by deficient activity of antioxidant enzymes, for example, heme oxygenase (HO). 2226 …”
Section: Introductionmentioning
confidence: 99%